Source, migration and toxicology of microplastics in soil - Guo, Jing-Jie; Huang, Xian-Pei; Xiang, Lei; Wang, Yi-Ze; Li, Yan-Wen; Li, Hui; Cai, Quan-Ying; Mo, Ce-Hui; Wong, Ming-Hung (Environment international, 2020)
•Microplastic-induced changes affect soil function and soil microbial communities.•The effects of microplastics on soil or soil organisms depend on particle types, concentration and exposure time.•Consumption of microplastics can cause mechanical damage, chemical responses and disrupt gut microbial communities.•Microplastics have potential effects on plant growth and may accumulate and transport in plants.•Some bacteria biodegrade microplastics could be used for soil bioremediation. Microplastics are emerging contaminants and their presence in water and soil ecosystems has recently drawn considerable attention because they pose a great threat to entire ecosystems. Recent researches have focused on the detection, occurrence, characterization, and toxicology of microplastics in marine and freshwater ecosystems; however, our understanding of the ecological effects of microplastics in soil ecosystems is still limited compared with that in aquatic ecosystems. Here, we have compiled literature, studying the sources, migration of microplastics in soil, negative impacts on soil health and function, trophic transfer in food chains, and the corresponding adverse effects on soil organisms in order to address the potential ecological and human health risks caused by microplastics in soil. This review aims to address gaps in knowledge, shed light on the ecological effects of microplastics in soil, and propose future studies on microplastic pollution and the resultant soil ecotoxicity. Furthermore, this review is focused on limiting microplastics in soil and establishing management and remediation measures to mitigate the risks posed by microplastic pollution.